IMPACT OF FINANCIAL DISTRESS ON STOCK PRICE: THE CASE OF PULP & PAPER COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE - Augustina Kurniasih; Heliantono; Agus Herta Sumarto; Yulia Efni (UNUSA Press, 2022)
Cellulose is an organic component that is widely found in wood fibers. Cellulose is the main component in the pulp/paper industry. As in wood, the raw material for pulp contains cellulose fibers. Cellulose is often used and processed to produce various types in the paper industry. Pulp is the primary material for different paper products, ranging from factories’ boards to daily necessities such as paper, tissue, tea bags, and magazines. Meanwhile, paper is a new change in literature and language that has played a significant role in the history of the development of human civilization. The pulp and paper industry in Indonesia provides a reasonably good contribution to the Indonesian economy. Several pulp & paper companies are listed on the Indonesia Stock Exchange. The results of previous studies indicate that several pulp & paper companies are in a stage of financial difficulty. This study aims to prove empirically that the Z-score as a measure of the company's economic challenges affects stock prices. The results showed that the Z-score affected stock prices. From several ratios that make up the Z-score, it is known that the ratio of working capital to total assets, market value of equity to book value of debt, and sales to total assets have a significant effect on stock prices.